Do the host country's environmental regulations inhibit the enterprises' risk preference of multinational investment? Evidence from China. Issue 1 (1st January 2023) - Jiang, Hui; Peng, Cheng; Zou, Yu
Abstract: How to achieve a win-win situation between environment protection and economic development in the process of outward foreign direct investment (OFDI) has always been a major issue of Chinese enterprises. In recent years, China has paid unprecedented attention to environmental protection, and issued relevant policies to encourage enterprises to abide by the host country's environmental regulations and fulfil their environmental protection-related responsibilities in the process of going global. However, the influence of the host country's environmental regulations on the enterprises' risk preference of multinational investment (MIRP) has not received the attention it deserves. This article makes an empirical analysis on how the host country's environmental regulations affect the MIRP by using the sample of China's A-share listed companies from 2010 to 2019, and emphatically tests the mediating roles of enterprises' green technology innovation, environmental information disclosure and corporate environmental responsibility, and the moderating role of shareholder protection policies. It is found that, on the whole, the host country's environmental regulations will inhibit the MIRP by accelerating enterprises' green technology innovation, increasing the level of environmental information disclosure and promoting environmental responsibility. Besides, the shareholder protection policies of the host countries can positively moderate the influence of the host country's environmental regulations on the MIRP.